Evaluation of Appropriate Metatarsal Pad Length on Mechanical Parameters of Diabetic Foot Ulcer During Walking - Ebrahim Abdi; Mansour Islami; Mohammad Taghipour; Ali Bakhtiari (Biyumikānīk-i varzishī)
Objective: Studies have reported that the best strategy for reducing the peak pressure on metatarsals is to increase the surface area with the metatarsal pad. but the optimal length of metatarsal pads is still unclear. The purpose of this study was to evaluate the appropriate length of metatarsal pad and its effect on the reduction of diabetic foot ulcer mechanical parameters while walking. Methods: Participants were 15 male patients with diabetes mellitus (Mean±SD=63.3±2.01 years). Handmade metatarsal pads with a length equal to 18, 20, 23 and 25% of foot length were used. Patients wearing these pads passed the RS-scan foot scan in 5 separate conditions and their data were recorded. Repeated measures Analysis of Variance (ANOVA) was used for analyzing data. Results: Peak pressure significantly decreased in metatarsal regions 1, 3 and 4 (P=0.001), but no significant difference was observed in regions 2 and 5 (P<0.05). A significant difference was observed in pressure-time integral between the five conditions in all metatarsal pads (P=0.001), but its change between the type of pad and metatarsal region was different. In the metatarsal regions 1 and 2 with pads of 18 and 20% of foot length, the peak time pressure was significantly reduced, while in the pads of 23 and 25% of foot length, it significantly increased. In the metatarsal regions 3, 4 and 5 with a pad of 18% of foot length, the peak time pressure increased, while with the pads of 20, 23, and 25 of foot length, a reduction was observed. Conclusion: As the pad length increases, the pressure peak in the metatarsal areas decreases, but the effect of pad length on the time pressure depends on the metatarsal region and the pad length. The length of the pad relative to the size of the foot is a step forward for the insole design. Insole designers are recommended to use a metatarsal pad with 23% of foot length for diabetic patients.